MICROCIRCULATION IN THE AGGREGATED LYMPHOID NODULES IN PIG - Kikalova, Katerina; Charamza, Jiri; Kutal, Miroslav (Biomedical papers, 2006)
Aims: To compare the blood supply of the Peyer's patches in pigs with the already defined rodent one.Materials and methods: Pig tissue was used. Injections of india ink, microscopic examination of the histological preparations stained by a haematoxylin - eosin and scanning electron microscopy of the corrosive casts were used for the depiction of the vessels.Results: A model of the blood microcirculation of PP and its relation to the blood circulation of the small intestine was created. Only the capillaries in the follicles, but not the ascending arterioles as in rats were found.
Keywords: Peyer's patches/Pig/Microcirculation